Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 123550 by mnjuly1970 last updated on 26/Nov/20

           ....nice    mathematics...        evaluate ::::                  Ω=∫_0 ^( ∞) ((√(x+1)) −(√x) )^(10) dx=?

....nicemathematics...evaluate::::Ω=0(x+1x)10dx=?

Answered by Olaf last updated on 26/Nov/20

Let x = sinh^2 u  dx = 2sinhucoshudu = sinh(2u)du  Ω = ∫_0 ^∞ ((√(1+sinh^2 u))−(√(sinh^2 u)))^(10) sinh(2u)du  Ω = ∫_0 ^∞ (coshu−sinhu)^(10) sinh(2u)du  Ω = ∫_0 ^∞ (e^(−u) )^(10) ((e^(2u) −e^(−2u) )/2)du  Ω = ∫_0 ^∞ ((e^(−8u) −e^(−12u) )/2)du  Ω = [((−(1/8)e^(−8u) +(1/(12))e^(−12u) )/2)]_0 ^∞   Ω = −(1/2)(−(1/8)+(1/(12)))  Ω = (1/(48))

Letx=sinh2udx=2sinhucoshudu=sinh(2u)duΩ=0(1+sinh2usinh2u)10sinh(2u)duΩ=0(coshusinhu)10sinh(2u)duΩ=0(eu)10e2ue2u2duΩ=0e8ue12u2duΩ=[18e8u+112e12u2]0Ω=12(18+112)Ω=148

Commented by mnjuly1970 last updated on 26/Nov/20

excellent mr olaf.thank you..

excellentmrolaf.thankyou..

Answered by MJS_new last updated on 26/Nov/20

∫((√(x+1))−(√x))^(10) dx=       [t=((√(x+1))−(√x))^(10)  → dx=−(((√x)(√(x+1)))/(5((√(x+1))−(√x))^(10) ))dt]  =(1/(20))∫((t^(2/5) −1)/t^(1/5) )dt=(t^(6/5) /(24))−(t^(4/5) /(16))  borders for x: [0; ∞) ⇒ borders for t: [1; 0]  ⇒ answer is (1/(48))

(x+1x)10dx=[t=(x+1x)10dx=xx+15(x+1x)10dt]=120t2/51t1/5dt=t6/524t4/516bordersforx:[0;)bordersfort:[1;0]answeris148

Commented by MJS_new last updated on 26/Nov/20

∫_0 ^∞ ((√(x+1))−(√x))^n dx=(2/(n^2 −4)) at least for n∈N∧n>2

0(x+1x)ndx=2n24atleastfornNn>2

Commented by MJS_new last updated on 26/Nov/20

...it holds for n∈R∧n>2

...itholdsfornRn>2

Commented by mnjuly1970 last updated on 26/Nov/20

grateful mr MJS..

gratefulmrMJS..

Commented by mnjuly1970 last updated on 26/Nov/20

Answered by mathmax by abdo last updated on 26/Nov/20

let I_n =∫_0 ^∞ ((√(x+1))−(√x))^n  dx  changement x=sh^2 t give  I_n =∫_0 ^∞   (ch(t)−sh(t))^n 2sh(t)cht dt  =∫_0 ^∞ (((e^t  +e^(−t) )/2)−((e^t −e^(−t) )/2))^n  sh(2t)dt  =∫_0 ^∞  e^(−nt)  ×((e^(2t) −e^(−2t) )/2) dt =(1/2)∫_0 ^∞  (e^(−(n−2)t) −e^(−(n+2)t) )dt  =(1/2)[−(1/(n−2))e^(−(n−2)t) +(1/(n+2))e^(−(n+2)t) ]_0 ^∞   =(1/2){(1/(n−2))−(1/(n+2))}=(1/2)×((n+2−n+2)/(n^2 −4))=(2/(n^2 −4))  n=10 ⇒ ∫_0 ^∞ ((√(x+1))−(√x))^(10) dx =(2/(100−4))=(2/(96))=(1/(48))

letIn=0(x+1x)ndxchangementx=sh2tgiveIn=0(ch(t)sh(t))n2sh(t)chtdt=0(et+et2etet2)nsh(2t)dt=0ent×e2te2t2dt=120(e(n2)te(n+2)t)dt=12[1n2e(n2)t+1n+2e(n+2)t]0=12{1n21n+2}=12×n+2n+2n24=2n24n=100(x+1x)10dx=21004=296=148

Commented by mnjuly1970 last updated on 27/Nov/20

thanks a lot sir max

thanksalotsirmax

Terms of Service

Privacy Policy

Contact: info@tinkutara.com